2018
DOI: 10.1002/jcp.27504
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of corneal sub‐basal nerve recovery after photorefractive keratectomy and influence of pars plana vitrectomy

Abstract: The corneal sub-basal nerve (SBN) plexus is destroyed during photorefractive keratectomy (PRK) and its recovery is still a matter of debate. In vivo confocal microscopy (IVCM) was used to evaluate SBN plexus in 23 patients at a distance of 10-25 years (mean 15.6 years) from myopic PRK. Because 8 out of the 23 PRK patients underwent pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment, IVCM was also performed on those patients 6 months after PPV. Thirteen patients matched for age and myopia served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Likewise, a previous study [51] found that subbasal nerves were morphologically altered and that they still did not achieve the preoperative values even 5 years after PRK. In a 15-20 year follow-up study [52], reduced corneal subbasal nerve density was observed in post-PRK eyes compared to that of controls, which also indicates incomplete nerve regeneration.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, a previous study [51] found that subbasal nerves were morphologically altered and that they still did not achieve the preoperative values even 5 years after PRK. In a 15-20 year follow-up study [52], reduced corneal subbasal nerve density was observed in post-PRK eyes compared to that of controls, which also indicates incomplete nerve regeneration.…”
Section: Discussionmentioning
confidence: 94%